ECG simulator monitor for teaching. - Tovar O., Adolfo; Kabela, E.; Valenzuela, F.; Rodriguez, G. (Revista Mexicana de Ingenieria Biomedica, 1988)
An ECG simulator that displays the signals on a modified conventional TV monitor is presented. The system is based on a previously designed control microcomputer (MC) in which blocks of complex electrocardiographic data were recorded in permanent memory, which can be arranged in some required sequence as a method of visualizing arrhythmias or normal ECG. The recording is made in X-Y vector form, transmitting from the MC the information to a D / A converter and power amplifier to the horizontal deflection coil. The vertical sweep is constant and controlled by the television itself, leaving the MC to synchronize this sweep and extinguish the beam at convenient points.